Evidences of stress and its consequences among Nepalese adolescents (Health Renaissance, 2013)
Background: Changing emotional and physical status along with increasing social, family and academic pressure lead to various impairments in mental health of adolescents. Objective: To examine the level of stress and its consequences in school going adolescences and examine adolescent’s adjustment at various places- home, school, peers, teachers and general matters. Methods: A descriptive and a single stage study were done at one of the school in Kathmandu Metropolitan. Every section of the class of the selected school was visited to explain the students about semi-structured pro forma, Student Stress Scale (SSS) and Pre-Adolescent Adjustment Scale (PAAS). The SSS was used to measure stresses faced by adolescents during last on year and PAAS measured their adjustments at places like home, school, peers, teachers and general matters. Results: 104 students participated in the study, male- 45, female- 59. Children with joint family type showed highest level of stress (mean 424.67; p=0.002). Among females, it is the broken family type which showed the highest level of stress (p=0.002). Among boys, second birth order showed highest level of stress (mean 382.31; p=0.005). Similarly among girls, it was first birth order (Mean 537.67; p=0.009). Among top 10 stressors labeled by students, highest stressor is death of a close family members followed by death of a close friend.Conclusion: Children during adolescent period undergo various stresses and adjustment and it depend upon their ability to cope with stress in various places like home, school, peers and teachers. Health Renaissance, January-April 2013; Vol. 11 No.1; 11-16 DOI: http://dx.doi.org/10.3126/hren.v11i1.7594